The GLP-1 receptor agonist Semaglutide decreases vascular inflammation in a rabbit model of advanced atherosclerosis. (25th November 2020) - Kildevang Jensen, J; Grandjean Poulsen, C; Binderup, T; Bentsen, S; Follin, B; Ripa, R; Kjaer, A
Abstract: Introduction: Atherosclerosis is one of the most common inflammatory disorders leading to cardiovascular disease. Incretin therapies such as Glucagon like peptide 1 (GLP-1) receptor agonists has demonstrated efficacy in reducing major adverse cardiovascular events among high risk populations, possibly due to a reduction in vascular inflammation. Positron emission tomography (PET) is a promising modality in the study of atherosclerosis since it has the ability to evaluate physiological processes in vivo. The somatostaton receptor 2 (SSTR2) targeting tracer [64Cu]Cu-DOTA-TATE (DOTATATE) has high specificity for activated macrophages, which are one on the key instigators of atherosclerosis. Two other radiotracers, more commonly used to study atherosclerosis are Na[18F]F (NaF) a radiotracer used for detection of vascular microcalcifications, and [18F]FDG (FDG) used for visualization of inflammatory metabolic activity. Purpose: The purpose of this study was to evaluate the anti-atherosclerotic and anti-inflammatory effects of the GLP-1 receptor agonist Semaglutide, using molecular imaging with DOTATATE, NaF and FDG, in a rabbit model of advanced atherosclerosis. Methods: A total of 23 female New Zealand White rabbits were fed a high cholesterol diet for 4 months and endothelial denudation of the aorta was performed twice (Fig 1A). The animals underwent baseline PET/CT scans using DOTATATE and FDG. They were then randomly allocated to an intervention group (n=12) or control group (n=11) receiving bi- weekly subcutaneous injections of either Semaglutide in a dose escalating regimen up to 44 μg/kg/week, or placebo (n=11). The intervention period was 16 weeks for both groups. At follow-up, the animals underwent PET/CT scans with DOTATATE, FDG and NaF. Regions of interest were drawn on all CT scans of the aorta from the right renal artery to the iliac bifurcation, and SUVmax was measured from the superimposed PET scans. Data are presented as means ± SEM. Results: SUVmax for FDG and DOTATATE were similar in the 2 groups at baseline (DOTATATE: 7.59±0.48 vs 6.69±0.28, P=0.13 and FDG: 2.63±0.12 vs 2.86±0.19 P=0.29). At follow-up, the Semaglutide group had a significantly lower uptake of both DOTATATE and FDG, although the largest difference was observed for DOTATATE (DOTATATE: 5.83±0.24 vs 7.10±0.33, P=0.001 and FDG: 2.49±0.13 vs 2.99±0.15, P=0.034) (Fig 1BC). Microcalcifications visualized using NaF PET, showed no difference at follow-up between the Semaglutide and the control group (4.15±0.30 vs 3.92±0.34, P=0.62) (Fig 1D). Increase in body weight was significantly attenuated in the Semaglutide group compared to the control group at follow-up (0.25±3.29% vs 10.68±3.01%, P=0.0016). Conclusions: Semaglutide decreases vascular uptake of the SSTR2 tracer, DOTATATE, and FDG but not NaF. This supports the hypothesis that Semaglutide reduces inflammation by means of decreased macrophage activity and metabolism in the arterial wall. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Department of Clinical Physiology, Nuclear Medicine & PET and Cluster for Molecular Imaging, Rigshospitalet and University of Copenhagen, Copenhagen, Denmark